Glecaprevir plus pibrentasvir for chronic hepatitis C virus genotype 1, 2, 4, 5, or 6 infection in adults with compensated cirrhosis (EXPEDITION-1): a single-arm, open-label, multicentre phase 3 trial. Issue 10 (October 2017) - Forns, Xavier; Lee, Samuel S; Valdes, Joaquin; Lens, Sabela; Ghalib, Reem; Aguilar, Humberto; Felizarta, Franco; Hassanein, Tarek; Hinrichsen, Holger; Rincon, Diego; Morillas, Rosa; Zeuzem, Stefan; et al.
Summary: Background: The once-daily, ribavirin-free, pangenotypic, direct-acting antiviral regimen, glecaprevir coformulated with pibrentasvir, has shown high rates of sustained virological response in phase 2 and 3 studies. We aimed to assess the efficacy and safety of 12 weeks of coformulated glecaprevir and pibrentasvir in patients with hepatitis C virus (HCV) infection and compensated cirrhosis. Methods: We did this single-arm, open-label, multicentre phase 3 study at 40 sites in Belgium, Canada, Germany, South Africa, Spain, and the USA. We enrolled patients aged 18 years or older with HCV genotype 1, 2, 4, 5, or 6 infection and compensated cirrhosis. Patients were either HCV treatment-naive or had not responded to treatment with interferon or pegylated interferon with or without ribavirin, or sofosbuvir plus ribavirin with or without pegylated interferon. Oral glecaprevir (300 mg) coformulated with pibrentasvir (120 mg) was administered once daily for 12 weeks. The primary efficacy endpoint was sustained virological response at post-treatment week 12 (HCV RNA <15 IU/mL). We assessed efficacy and safety in all patients who received at least one dose of study drug (intention-to-treat population). This study is registered withClinicalTrials.gov, numberNCT02642432 . Findings: Between Dec 7, 2015, and May 4, 2016, we enrolled 146 patients with compensated cirrhosis, of whom 48 (33%) had genotype 1a HCV infection, 39 (27%) had genotype 1b infection, 34 (23%) had genotype 2 infection, 16 (11%) had genotype 4 infection, two (1%) had genotype 5 infection, and seven (5%) had genotype 6 infection. 12 weeks after treatment, 145 patients (99%, 95% CI 98–100) achieved sustained virological response, with one (1%) relapse at post-treatment week 8. We recorded 101 (69%) adverse events, of which 65 (64%) were mild. The most common adverse events were fatigue (n=28 [19%]) and headache (n=20 [14%]). 11 (8%) patients had serious adverse events, none of which were deemed related to study drugs. No patients had elevations in alanine aminotransferase and no patients prematurely discontinued treatment because of adverse events. Interpretation: Our results show that 99% of patients treated with once-daily glecaprevir plus pibrentasvir achieved a sustained virological response at 12 weeks. Furthermore, this drug regimen had a favourable safety profile in previously treated or untreated patients with chronic HCV genotype 1, 2, 4, 5, or 6 infection and compensated cirrhosis. These findings could help simplify treatment algorithms and reduce treatment burden. Funding: AbbVie.